Estrogen receptor beta (ERß) In gastric cancer – A systematic review and meta-analysis - S. Peri; Y. Niv (Microbiota in Health and Disease)
Introduction: Gastric cancer represents a major public health challenge worldwide due to its significant morbidity and mortality rates. Among the factors associated with the development of gastric cancer, estrogen receptor beta (ERβ) has emerged as a potential therapeutic target. The aim of the study was to investigate the relationship between ERβ expression and gastric cancer.